ANALISIS PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT DAN KEADILAN ORGANISASI TERHADAP KOMITMEN ORGANISASIONAL - Linanjung, Yolanda Ardestya; Natoil, Heri; Irawati, Marsha Ayunita (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2024)
Competition in the business world is increasingly tight and competitive and achieves maximum profit. This study aims to determine the effect of perceived organizational support and organizational justice on organizational commitment. The independent variables are perceived organizational support (X1), organizational justice (X2) and the dependent variable is organizational commitment (Y). The population of this study was all 811 employees of PT Sam Kyung Jaya Busana in Boyolali Regency and the sample was 89 people. The data collection technique was a quantitative method using a questionnaire. For instrument testing using the Validity, Reliability, and Classical Assumption Tests. For data analysis techniques using multiple linear regression analysis methods with t-tests, Model Feasibility tests and Determination Coefficients (R2). The results of the study using multiple linear regression show the following regression equation: Y = 0.386 + 0.539X1 + 0.449X2. From the t-test, it is known that the Perceived Organizational Support variable has a significant positive effect on the organizational commitment variable, the organizational justice variable has a significant positive effect on the organizational commitment variable. The main suggestion for Organizational Leaders is to be able to motivate employees to master their work well according to supervisory directions with an orientation towards the results to be achieved later.